Associations between literacy and attitudes toward artificial intelligence–assisted medical consultations: The mediating role of perceived distrust and efficiency of artificial intelligence. (February 2023) - Yi-No Kang, Enoch; Chen, Duan-Rung; Chen, Yen-Yuan
Abstract: Artificial intelligence (AI) is increasingly used in health care. Understanding the factors associated with attitudes toward AI-assisted medical consultations is necessary. This study investigated the associations of health literacy, digital literacy, perceived distrust, and efficiency of AI with attitudes toward AI-assisted medical consultations by using a sample of the general population in Taiwan. Data were collected through an online survey between July and September 2020. A health literacy scale comprising three dimensions (health care, disease prevention, and health promotion) and a digital literacy scale were employed. Path analysis was performed to identify direct and indirect associations between health literacy and digital literacy, perceived distrust, the efficiency of AI, and attitudes toward AI-assisted medical consultations. In total, 1363 respondents completed the questionnaire. Two health literacy dimensions were directly associated with attitudes toward AI-assisted medical consultations, and the association was mediated by perceived distrust and the efficiency of AI. The association between digital literacy and attitudes toward AI-assisted medical consultations was fully mediated by perceived distrust of AI and its efficiency. Emotional perceptions are essential in the association between digital literacy and attitudes toward AI-assisted medical consultations. These results highlight the importance of subjective evaluations of AI used in doctor-patient interactions. Highlights: Health literacy may directly and positively affect attitudes toward AI-assisted medical consultation. Perceived distrust of AI is an essential factor between literacy and attitudes toward AI-assisted medical consultation. Perceived efficiency of AI is an essential factor between literacy with attitudes toward AI-assisted medical consultation.